2021
DOI: 10.1515/ijfe-2021-0186
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, structural and physicochemical properties of rice starch nanoparticles prepared via ultra-high pressure homogenization

Abstract: Native rice starches were treated with five periods of ultra-high pressure homogenization (UHPH) under each of 60, 80, 100, 120, 140 and 160 MPa, respectively. The morphological, structural and physicochemical properties of starches treated with UHPH were examined. The mean particle diameter of starch nanoparticles ranged between 154.20 and 260.40 nm. SEM revealed that the granular amorphous region of starch granules was damaged under pressures between 60 and 80 MPa, and the crystalline region was further dest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…The samples of UDT‐60, UDT‐80, UDT‐100, UDT‐120, UDT‐140, and UDT‐160 contained the atactic lumps with an uneven and tiny pore structure. Our previous study suggested that the shear, cavitation, and turbulence effects produced by UHPH can destroy starch granules, causing the damage of amorphous regions under 60–100 MPa and the destruction of crystalline regions under 120–160 MPa (Sun et al, 2021). More importantly, UHPH disrupted the hydrogen bonds and glycosidic bonds between starch molecules, which resulted in the degradation of amylopectin molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples of UDT‐60, UDT‐80, UDT‐100, UDT‐120, UDT‐140, and UDT‐160 contained the atactic lumps with an uneven and tiny pore structure. Our previous study suggested that the shear, cavitation, and turbulence effects produced by UHPH can destroy starch granules, causing the damage of amorphous regions under 60–100 MPa and the destruction of crystalline regions under 120–160 MPa (Sun et al, 2021). More importantly, UHPH disrupted the hydrogen bonds and glycosidic bonds between starch molecules, which resulted in the degradation of amylopectin molecules.…”
Section: Resultsmentioning
confidence: 99%
“…The starch was dispersed in water to form a suspension (3%, w/v) that was homogenized for 5 cycles under pressures of 0, 60, 80, 100, 120, 140, and 160 MPa using an ultra-high pressure homogenizer (APV-2000, Beijing Udare Technology Co., Ltd., China) equipped with a water circulation temperature control system (Sun et al, 2021). The temperature of the entire process was maintained below 30 C. After freeze-drying, the samples were pulverized, passed through a 100-mesh sieve and stored in a desiccator.…”
Section: Preparation Of Sample Via Uhphmentioning
confidence: 99%